Role of endothelial hyaluronan in peritoneal membrane transport and disease conditions during peritoneal dialysis - Keisuke Kamiya; Naoyuki Hatayama; Mitsuhiro Tawada; Akimasa Asai; Mai Yamauchi; Hiroshi Kinashi; Shunnosuke Kunoki; Makoto Yamaguchi; Masashi Mizuno; Yasuhiro Suzuki; Masataka Banshodani; Takuji Ishimoto; et al. (Scientific Reports, 2024)
Abstract Peritoneal membrane dysfunction in peritoneal dialysis (PD) is primarily attributed to angiogenesis; however, the integrity of vascular endothelial cells can affect peritoneal permeability. Hyaluronan, a component of the endothelial glycocalyx, is reportedly involved in preventing proteinuria in the normal glomerulus. One hypothesis suggests that development of encapsulating peritoneal sclerosis (EPS) is triggered by protein leakage due to vascular endothelial injury. We therefore investigated the effect of hyaluronan in the glycocalyx on peritoneal permeability and disease conditions. After hyaluronidase-mediated degradation of hyaluronan on the endothelial cells of mice, macromolecules, including albumin and β2 microglobulin, leaked into the dialysate. However, peritoneal transport of small solute molecules was not affected. Pathologically, hyaluronan expression was diminished; however, expression of vascular endothelial cadherin and heparan sulfate, a core protein of the glycocalyx, was preserved. Hyaluronan expression on endothelial cells was studied using 254 human peritoneal membrane samples. Hyaluronan expression decreased in patients undergoing long-term PD treatment and EPS patients treated with conventional solutions. Furthermore, the extent of hyaluronan loss correlated with the severity of vasculopathy. Hyaluronan on endothelial cells is involved in the peritoneal transport of macromolecules. Treatment strategies that preserve hyaluronan in the glycocalyx could prevent the leakage of macromolecules and subsequent related complications.